plsss na terazzz

3x+7x=

4a-6a=
2y-y+3y=
4/7*0,7x=
3,5x:5=
2,3x:3=
-y/5*5/3=


Odpowiedź :

1)

[tex]3x+7x=10x[/tex]

2)

[tex]4a-6a=-2a[/tex]

3)

[tex]2y-y+3y=4y[/tex]

4)

[tex]\frac{4}{7}*0,7x=\frac{4}{7}*\frac{7}{10}x=2*\frac{1}{5}x=\frac{2}{5}x[/tex]

5)

[tex]3,5x:5=0,7x[/tex]

6)

[tex]2,3x:3=\frac{23}{10}x:3=\frac{23}{10}*\frac{1}{3}x=\frac{23}{30}x[/tex]

7)

[tex]-\frac{y}{5}*\frac{5}{3}=-y*\frac{1}{3}=-\frac{1}{3}y[/tex]

Odpowiedź:

w załączniku ;)

Szczegółowe wyjaśnienie:

mam nadzieję że pomogłam :D

Zobacz obrazek Aksolotl23